Encyclopedia of democratic thought - Clarke, Paul A. B., 1946-; Foweraker, Joe (Routledge, 2001)
Containing almost 200 entries the Encyclopedia of Democratic Thought explores all the ideas that matter to democracy. It is destined to become the first port-of-call for all students, teachers and researchers of political science.